2020
DOI: 10.1002/ctm2.205
|View full text |Cite
|
Sign up to set email alerts
|

Low‐glucose‐sensitive TRPC6 dysfunction drives hypoglycemia‐induced cognitive impairment in diabetes

Abstract: • TRPC6 expression is specifically sensitive to glucose in a concentrationdependent manner. • Recurrent moderate hypoglycemia impairs cognitive function by inhibiting hippocampal TRPC6. • Repression of TRPC6 promotes hippocampal mitochondrial fission via inhibition of AMPK. • Activation of TRPC6 by hyperforin prevents recurrent moderate hypoglycemia-induced cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…Currently, there are some controversial results on this issue, because insulin could cause hypoglycemia related cognitive damage in patients with T2DM. 31 , 32 Importantly, GLP‐1 RA activation was found to increase in the cAMP levels leading to the modulation of downstream kinases that are related to growth factor signaling, which may thereby restore brain insulin resistance and reduce levels of amyloid‐β peptide. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are some controversial results on this issue, because insulin could cause hypoglycemia related cognitive damage in patients with T2DM. 31 , 32 Importantly, GLP‐1 RA activation was found to increase in the cAMP levels leading to the modulation of downstream kinases that are related to growth factor signaling, which may thereby restore brain insulin resistance and reduce levels of amyloid‐β peptide. 26 …”
Section: Discussionmentioning
confidence: 99%
“…TRPC6 is expressed in many different brain regions, such as the cortex, hippocampus, cerebellum, basal ganglia, thalamus, hypothalamus, and dorsal root ganglia [ 57 ]. Numerous studies have documented that the expression of TRPC6 in primary cultured neurons or neuronal cell lines is protective under various stress conditions [ 48 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Cell-specific Roles Of Trpc6mentioning
confidence: 99%
“…A growing body of evidence indicates a link between impaired glucose metabolism in the central nervous system and AD [17,[64][65][66]. It was shown that reduced glucose availability in the brain directly triggers behavioral deficits by promoting the development of tau neuropathology and synaptic dysfunction [17,18].…”
Section: Comparative Analysis Of the Gene Network Of Hypoglycemia Cognitive Decline And Admentioning
confidence: 99%